The study of swimmers's hand and forearm using computational fluid dynamics - Marinho, D.; Leal, L.; Sousa, L.; Reis, V.; Alves, F.; Vilas-Boas, J. P.; Rouboa, A.; Silva, A. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Computational Fluid Dynamics has been widely used in biomechanics studies applied to medicine and sport. In this study we developed a 3-D model for swimmer`s hand/forearm forces using Computational Fluid Dynamics. Models used in the simulations were created in CAD, based on realistic dimensions of a right adult human hand/forearm. The governing system of equations considered was the incompressible Reynolds averaged Navier-Stokes equations implemented with Fluent® code. The drag coefficient was the main responsible for propulsion, with a maximum value of force propulsion corresponding to a pitch angle of 90º. The lift coefficient seemed to play a less important role in the generation of propulsive force with pitch angles of 0º and 90º but it is important with a pitch angle of 45º. It was demonstrated the relevance of applying CFD in the propulsive force measurements, using a more realistic model of a human segment.